Intellectual Property Rights: Legal Protection in Copyright of Creative Media State Polytechnic Research Products - Haryo Adiyatman Wicaksono; Pandu Adi Cakranegara (IHSA Institute, 2022)
ALegal protection for copyright regulated by law number 28 of 2014 is also included in intellectual property rights (IPR). The world of education, especially vocational education, plays a role in creating products that can innovate and benefit the industry later. The work results can be in the form of finished products that many people will use. The existence of legal protection for vocational academics is very much needed. This will later be helpful for product rights created by themselves and registered in the eyes of the law in Indonesia. This research uses qualitative research and normative juridical research, both primary and secondary. The data collection technique is done using library studies.